A systematic review of the effects of laughter on blood pressure and heart rate variability - Oliveira, R.; Arriaga, P. (Humor - International Journal of Humor Research, 2022)
In this systematic review, we sought to understand the effects of laughter-inducing interventions on blood pressure and heart rate variability. For this purpose, we identified 32 relevant records through database searching. The results suggest that laughter is associated with a decrease in blood pressure in pre–post measurements. However, this association varies according to the type of intervention delivered and the characteristics of participants. In controlled between-groups comparisons, the effect of laughter-inducing interventions on blood pressure was found to be non-significant, which can be due to the small number of studies available and its high level of heterogeneity. In studies involving heart rate variability, the most consistent findings point to an association between laughter and decreases in both frequency (LF/HF) and time-domain (SDNN) indicators. Longitudinal studies suggest that laughter frequency is associated with improved cardiovascular health. Several studies presented sub-optimal levels of quality, and more research is necessary to examine the impact of individual and intervention-related factors in the effectiveness of laughter-inducing interventions in cardiovascular health.